Assessing the financial state of construction enterprises - Ginevičius, Romualdas; Podvezko, Valentinas (Technological and Economic Development of Economy, 2006)
The financial state of construction enterprises can be described by a set of criteria evaluating their commercial activity from various perspectives. The most important of them are solvency and financial risk, including the ratio of current assets to current liabilities, the ratio of current assets minus stocks to current liabilities, the ratio of equity to liabilities, the ratio of assets to liabilities and the ratio of current assets to equity. These values indicate how efficiently various resources, i. e. finances, materials, manpower, etc. are used at an enterprise. The criteria characterizing the financial state of an enterprise from various perspectives may change in different directions. Moreover, these criteria are multidimensional. Therefore, a problem of finding a unified approach to describe this conflicting situation arises. The particular criteria describe the particular aspects of a complex object. To obtain an integrated estimate of a considered object, multicriteria evaluation methods are applied. Being versatile, these methods are used for solving various problems. A great number of methods evaluating the performance of multidimensional objects have been created and used recently. Each method has some advantages in describing the particular features of an object. Most methods use various techniques for normalization or transformation of the initial data. In the present investigation seven methods of multicriteria evaluation are applied. The calculations made yielded actually the same results, except those obtained by two methods – the sum of ranks and VIKOR. However, the deviation of the data obtained by using these methods from the average value was small. The priority order of enterprises is finally determined integrating the results obtained by all methods used in the present analysis.Statybos įmonių finansinės būklės kompleksinis įvertinimasSantrauka. Finansinę statybos įmonių būklę apibūdina daug rodiklių, kurie įvairiais aspektais parodo įmonių komercinės veiklos rezultatus. Labai svarbi vieta tarp jų tenka mokumo ir finansinės rizikos rodikliams. Jiems priklauso einamojo, kritinio, bendrojo likvidumo, įsiskolinimo bei manevringumo koeficientai. Savo esme šie dydžiai rodo įmonės finansinių, medžiaginių, darbo bei kitokių išteklių naudojimo laipsnį. Minėtieji įvairius įmonės finansinės būklės aspektus apibūdinantys rodikliai kinta priešingomis kryptimis. Be to, jų dimensijos taip pat gali skirtis. Kyla klausimas – kaip tokioje prieštaringoje situacijoje sudaryti apibendrinamąjį vaizdą. Į sudėtingą reiškinį apibūdinančius rodiklius žiūrima kaip į dalinius, perteikiančius esminius jo aspektus. Siekiant apibendrintai įvertinti nagrinėjamą reiškinį, taikomi daugiakriteriniai metodai. Dėl savo universalumo jie taikomi įvairių sričių uždaviniams spręsti. Šiuo metu sukurta ir taikoma daug sudėtinių dydžių veiklos efektyvumo kompleksinio įvertinimo metodų. Kiekvienas metodas turi savo privalumų ir išryškina atskiras šių dydžių ypatybes. Dauguma šių metodų pagrįsti skirtinga pradinių duomenų normalizacija arba jų transformacija. Šiame darbe taikyti septyni daugiakriterinio įvertinimo metodai. Apskaičiavus gautas tas pats rezultatas, išskyrus du metodus – vietų sumą ir VIKOR. Kita vertus, ir jie parodė tik nežymų nuokrypį nuo vidurkio. Galutinis įmonių prioritetas nustatomas sujungus visų taikytų metodų rezultatus.Reikšminiai žodžiai: statybos įmonė, finansinės būklės įvertinimas, daugiakriteriniai metodai.First Published Online: 21 Oct 2010